MicroRNA223 promotes pathogenic T‐cell development and autoimmune inflammation in central nervous system in mice. Issue 4 (29th June 2016) - Satoorian, Tiffany; Li, Bo; Tang, Xiaolei; Xiao, Jidong; Xing, Weirong; Shi, Weixing; Lau, Kin‐Hing William; Baylink, David J.; Qin, Xuezhong
Summary: Multiple sclerosis (MS) is an incurable central nervous system autoimmune disease. Understanding MS pathogenesis is essential for the development of new MS therapies. In the present study, we identified a novel microRNA (miR) that regulates experimental autoimmune encephalomyelitis (EAE), an animal model of MS. Expression of miR223 was up‐regulated specifically in spinal cords and lymphoid organs but not in other examined tissues. A global miR223 knockout (miR223 −/− ) in mice led to a significant delay in EAE onset, reduction in spinal cord lesion, and lessening of neurological symptoms. These protective effects could be reproduced in bone marrow chimeras reconstituted with miR223 −/− haematopoietic stem cells. We also found that miR223 deficiency reduced T helper type 1 (Th1) and Th17 infiltration into spinal cords. To address underlying mechanisms, we investigated the role of miR223 in regulating the function, development and interaction of the major immune cells. Expression of the genes associated with dendritic cell (DC) activation (CD86 and MHC II) and Th1 and Th17 differentiation [interleukin‐12 (IL‐12) and IL‐23, respectively] was significantly decreased in the spleens of miR223 −/− mice bearing EAE. The miR223 −/− DCs expressed significantly lower levels of basal and lipopolysaccharide‐induced IL‐12 and IL‐23 compared with the wild‐type DCs. These data are consistent with the observed lower efficiency of miR223 −/− DCs to support Th1 and Th17 differentiation from naive T cells over‐expressing an EAE antigen‐specific T‐cell receptor. Our data suggest that miR223 promotes EAE, probably through enhancing DC activation and subsequently the differentiation of naive T cells toward Th1 and Th17 effector cells.